COP28 Resilience Hub Synthesis Report: Key Messages and Future Directions - Resilience Hub; Angheloiu, Corina; Clarke, Sarah; Ginoya, Namrata; González, David; Queiroz, Cibele; Vora, Shuchi (2023)
This report synthesises the key findings and recommendations for action from the COP28 Resilience Hub and aims to help set the direction for future action towards COP29 and beyond. The report first provides an overview of the key adaptation and resilience decisions and announcements that took place during COP28; it then presents the key messages and findings from the events of the Resilience Hub and offers concluding remarks and a guidepost for the year ahead.